In Vitro Study of the Effect of Vanillin Derivatives on Aryl Esterase, Troponine and Lipid Profile in Atherosclerosis Patients as Compared to Normal Subjects - Atallah, Murooj Mousa; Khalid, Fadhil Dawood; Sulaiman, Yaser A.M. (Tikrit Journal of Pharmaceutical Sciences, 2023)
The study describes the effect of vanillin derivative on the activity of aryl esterase in vitro. After that, the Estimated effectiveness of the enzyme aryl esterase, troponin T, and lipids. The research included the collection of 120 blood samples distributed to 60 blood samples of healthy people as a control group and 60 blood samples of patients with atherosclerosis who were diagnosed under the supervision of specialized doctors at Salah Eddin General Hospital / Catheterization Unit. Results showed that the vanillin derivative has an invigorating effect on the activity of aryl esterase, and that the degree of enzyme activation increases with the increase in the concentration of the derivative, while there was lower with a probability level (P≤ 0.0006) in the activity of aryl esterase from the serum of patients with atherosclerosis in addition, a significant increase at the probability level ( P ≤ 0.001) in the level of total cholesterol, triglycerides, LDL-C and VLDL-C, while there was decrease at the probability level (P ≤ 0.0004) in the level of HDL-C. Keywords: Aryl esterase, Vanillin derivative, Lipids, Atherosclerosis.